Literacy analysis of digital financial inclusion of zakat, Infaq, Alms and Religious Social Affairs (Ziska) at Lazismu Sangkapura Branch, Gresik Regency - Saputra, Sawaluddin Eka; Setiadi, Iwan; Rahmat, Rahmat; Aiyub Anshori (International Journal on Social Science, Economics and Art, 2024)
Many studies in the banking sector have explained the significant increase in digital technology-based financial inclusion because it is able to exceed targets, increase people's financial understanding and provide easy access to financial products and services. However, little research was found in the unbanked sector that could be a consideration for increasing financial inclusion in digital technology. This article aims to analyze the use of digital media, human resource capabilities in using digital media, and digital fund fundraising strategies towards digital financial inclusion literacy of zakat, infaq, alms and social religion (ziska) in Lazismu Sangkapura, Gresik Regency. This research uses a descriptive-phenomenological approach with qualitative methods. The sampling technique uses purposive sampling. Data collection procedures include literature study, observation, interviews and documentation. The analytical tool uses SWOT analysis to test the validity of the data against the research objectives. This research found that Lazismu Sangkapura has used the digital space for Ziska financial inclusion literacy less than optimally. Several practical analyzes identified that digital platforms are limited to m-banking transfers, individual resources are less skilled or trained in operating digital media, fundraising strategies implemented through digital programs have a positive trend of growing ziska fund acquisition and equitable distribution. Various inhibiting factors must be addressed comprehensively, such as institutional management, media, resources and strategies for realizing Ziska digital financial inclusion literacy.